Being Monolingual in a Multilingual Space: An Autoethnographic Exploration of Educational Experiences - Mathabata, Colleen Ashlin; Munir, Fouzia (JOLLT Journal of Languages and Language Teaching, 2025)
This study aims to explore the challenges of being monolingual in multilingual spaces, regardless of which language is an individual’s home language. The study focuses on South African educational institutions. South Africa is a multilingual country with a monolingual history. During the apartheid era in South Africa, Afrikaans was imposed as the official language; post-apartheid, English is the dominant language in the country. This is problematic because South Africa is a diverse country with 12 official languages, yet monolingualism still prevails, causing language barriers in different spaces. The study utilises a qualitative, autoethnographic approach to describe lived experiences of monolingualism. It contributes to understanding how monolingual policies in educational spaces affect the students directly. There is very little research about the monolinguistic perceptions of students studying in multilinguistic contexts. Thus, this study examines the autoethnographic experiences of two educational contexts, secondary school and university, through the eyes of the first author. Thematic analysis is used to analyse these experiences regarding the challenges of monolingualism and the need for multilingualism in a diverse context. Findings show that monolingualism causes barriers to communication and affects students’ academic success. They struggle to navigate through educational spaces where the medium of instruction is a language other than their home language. They are limited in their interactions when they cannot speak the language being used. A diverse educational space needs multilingualism to benefit individuals, academically and socially. This has implications for educational policies and practices. In order to help students benefit from their educational experience and to prepare them for a multilingual society, focused attention should be given to inclusive language policies and the implementation thereof. In addition, there is a dire need to change negative language attitudes, since positive language attitudes promote multilingualism.